НАЦИОНАЛЬНЫЕ АРХЕТИПЫ «ЖЕНСТВЕННОСТИ»: СРАВНИТЕЛЬНЫЙ АНАЛИЗ УКРАИНСКОЙ И РУССКОЙ МОДЕЛЕЙ - Суковатая, Виктория (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 1970)
Анализируются исторические и социокультурные условия формирования моделей«женственности» в Украине и России. Делается вывод, что различия в понимании«женственности» обусловлены разницей национальных характеров и спецификой развитиястран, что в ХХ веке привело к разному наполнению идеи «феминизма» и степени егоприемлемости в обществах.Аналізуються історичні і соціокультурні умови формування моделей «жіночності» вУкраїні і Росії. Робиться висновок, що відмінності в розумінні «жіночності» обумовлені різницеюнаціональних характерів і специфікою розвитку країн, що в ХХ столітті привело до різногонаповнення ідеї «фемінізму» і міри його прийнятності в суспільствах.Viktoria Sukovataya. The National Archetypes of “femininity”: the comparative analyses ofUkrainian and Russian models. It is analyzed the models of "femininity" in Ukraine and Russia and thehistorical and socio-cultural conditions of their formation. It is concluded that the distinctions in notionsof "femininity" are caused by a differences of national characters and development of the countries.There was resulted in the 20th century in different understanding of Feminism and its legitimating insocieties.